Grants as a Model of Inheritance Prospective Distribution in the Coastal Santri Community - Ali Muhtarom; Yuli Sutoto Nugroho (Al-Ahkam, 2022)
The practice of Islamic inheritance law in Muslim communities in Indonesia experiences many obstacles. One of the reasons is that there is still a tradition of distribution of assets when parents are still alive and the prevailing kinship system. It was found in transferring property to the coastal santri community in Pekalongan City. This paper reveals the method of dividing the prospective inheritance of the coastal santri community and the mechanism for resolving disputes in the event of a dispute. This article uses a qualitative socio-legal studies approach and is descriptive and analytic. This article finds two things. First, the model for distributing the assets of the coastal santri community in Pekalongan City is carried out using grants orally and deliberation for consensus. Prospective inheritance is divided by the grant system equally, without distinguishing between men and women. The dispute resolution mechanism is carried out in negotiation and mediation.